Toxicidad del extracto metanólico de ají por ingestión del caracol manzana pomacea canaliculata en el cultivo de arroz - Hoyos Espinoza, Erick Fernando (2014)
In the plant health laboratory of CIAP of agricultural sciences faculty of the Technical University of Machala, in the period of october to december 2013 was the research on to determine the methanolic extracts of chili against adult stages Snail Pomacea caniculata, considering the next objectives: 1. Determine the effectiveness of aji botanical extract to control the snail Pomacea caniculata, 2. An economic analysis of the treatment. The treatments investigated in the bioassay were: T1 aji 120, 150 and 180ml per liter of wáter and absolute control. And in a second test dose was increased to 150, 180 and 200 ml of hot pepper extract per liter of water and absolute control. The variables analyzed were: weight in grams of cabbage consumed, percent of mortality, number of oviposition, which had a frequency of 48 hours. The chili oil extraction was performed by soxhlet team of three balls graduated of 250 ml; the nuts were ground and the powder was placed in cellulose thimbles. The extraction rough eight hours; the snails in adulthood were collected in rice cultivation in the province of Guayas conditioning them in expluma flex boxes. The experimental units composed of 10 adult specimens of Pomacea caniculata were fed leaf segments cabbage slaw sprinkled with chili prepared and kills slug. The experimental design used for the analysis of the variables was completely at random with five treatments and four replications. The extracts of capsicum or chili pepper formulated as an aqueous suspension at a rate of 2 % mortality achieved up to 65 % of adult snails Pomacea caniculata applied to cabbage leaves aqueous cabbage suspension. Another side effect of capsaicin pepper and other compounds influenced the reduction of oviposition and sealing of limestone structures that protect them. The slug kills formulated as metaldehyde granules and inert substances confirmed to be the best product for the complete mortality of specimens of Pomacea caniculata by supplying al sheets impregnated with an aqueous spray of 0,37% commercial product.